Economic Disputes Resolving Models by Courts in the Post-Soviet Countries - BUTYRSKY, ANDREY A.; NIKOLENKO, LYUDMILA N.; IVANYUTA, NATALYA V.; BUTYRSKAYA, IRINA A.; KABENOK, YULIA V. (The journal of contemporary issues in business and government, 2021)
The article is devoted to the study of models for resolving economic disputes by courts in the countries of the post-Soviet space (i.e. individual countries). Commercial courts should be viewed as a product of the historical development not only of the Soviet Union but also of European states since commercial courts first appeared in Western Europe and then spread throughout the continent. In this article, the authors examined the judicial systems of Ukraine, the Republic of Lithuania, the Republic of Armenia, the Republic of Kazakhstan, the Russian Federation, and the Republic of Belarus. The choice of these states was made taking into account the fact that they were all part of the Soviet Union, that is, they had the same initial elements of the judicial system, but at the moment, economic disputes are resolved differently in all these states. Based on the results of the study, the authors conclude that the following models of resolving economic disputes by courts can be distinguished as 1) economic disputes are resolved by economic courts based on the norms of the Economic Procedure Code (in this case, the status of economic courts can be determined in the Constitution or a special law); 2) economic disputes are resolved by economic courts based on the norms of the Civil Procedure Code; 3) economic disputes are resolved by general courts based on the norms of the Civil Procedure Code, and 4) certain economic disputes are resolved by the bankruptcy courts based on insolvency legislation.